CNJ's actions to combat human trafficking (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The present article aims to describe the initiatives developed by National Justice Council to monitor the progress of lawsuits, in Brazilian Justice, on human traffi cking, by proposing ways to give to speed up, as well as to contribute for greater effectiveness of judicial decisions on this issue.
Keywords: trafficking in persons; lawsuits; national council of justice